Dissociative electron attachment in C2H via electronic resonances. (17th November 2021) - Gulania, Sahil; Krylov, Anna I.
Abstract : Investigation of microwave-activated CH 4 /H 2 plasma used in chemical vapour deposition of diamond revealed the presence of electronically excited C 2 − ∗ (B 2 Σ u + ). Using high-level electronic structure methods, we investigate electronic structure of C 2 H − and suggest possible routes for the formation of C 2 − in the ground (X 2 Σ g + ) and excited (B 2 Σ u + ) states via electronic resonances. To describe electronically metastable states, we employ the equation-of-motion coupled-cluster method augmented by the complex absorbing potential. The resonance wavefunctions are analysed using natural transition orbitals. We identified several resonances in C 2 H −, including the state that may lead to C 2 − ∗ (B 2 Σ u + ). GRAPHICAL ABSTRACT: UF0001